Respuesta :

Answer:

0.64

Step-by-step explanation:

Given the sides of a triangle, we can solve for any angle using the Law of Cosines: [tex]a^2=b^2+c^2-2bc(cosA)[/tex]

Our variables:

a = 27

b = 36

c = 45

B = 90°

[tex]a^2=b^2+c^2-2bc(cosA)[/tex]

[tex](27)^2=(36)^2+(45)^2-2(36)(45)(cosA)[/tex]

[tex]720=1296+2025-3240(cosA)[/tex]

[tex]720-3321=-3240(cosA)[/tex]

[tex]-2601=-3240(cosA)[/tex]

[tex]\frac{2601}{3240} =cosA[/tex] ≈ [tex]0.80278[/tex]

[tex]cos^-(A)=cos^-(\frac{2601}{3240})[/tex]

[tex]< A = 0.63885708[/tex]

This might be wrong, but you get the method. I would repost for a better answer from someone else because I'm practically half asleep. Very sorry but I hope you get some help soon! Best of luck

Ver imagen Аноним